A coordinated control of hydraulic hub-motor auxiliary system for heavy truck. (April 2021) - Song, D.F.; Yang, D.P.; Zeng, X.H.; Zhang, X.M.; Gao, F.W.
Highlights: A hydraulic hub-motor auxiliary system (HHMAS) is used in the traditional trucks. Based on the HHMAS, a coordinated control algorithm is designed. The designed pump displacement control method is real-time in real vehicle test. HHMAS has a good effect on the control strategy presented in this paper. Abstract: To solve the contradiction between the trafficability and the power of traditional heavy trucks, the study proposes a coordinated control of hydraulic hub-motor auxiliary system for heavy truck to make full use of the coefficient of ground aadhesion and engine power. With hydraulic hub-motor auxiliary system (HHMAS) in the non-drive front wheels, the front wheels drive the truck on bad roads to ensure the trucks tractive capacity and exit on good roads to achieve better transmission efficiency. Based on the HHMAS, a wheel speed coordinated control strategy that considers slip efficiency to make system work effectively is designed. The pump displacement composite control method in the real vehicle is tested, the steady-state error is basically within 0.03. Experimental results show that HHMAS has a good effect on the control strategy presented. Hence, the study on HHMAS is a valuable to hydraulic hybrid application.